Evaluasi User Experience Sistem Informasi SI-SELMA Menggunakan User Experience Questionnaire (UEQ) - Haddad Alwi Situmorang; M. Khalil Gibran; Windy Halmania Hasibuan; Boi Dahlan Syahputra Padang; Amelia Sni Ramud (TIN: Terapan Informatika Nusantara, 2026)
The Student Electronic Correspondence Information System (SI-SELMA) is a digital administrative platform implemented by Universitas Islam Negeri Sumatera Utara to facilitate the management and issuance of various academic documents online. Although the system is operational and plays a crucial role in campus bureaucracy, no empirical evaluation has been conducted regarding the quality of its user interaction. This study aims to evaluate the user experience of SI-SELMA using the User Experience Questionnaire (UEQ) approach. Methodologically, this study employs a descriptive quantitative survey design, involving 147 active students from Universitas Islam Negeri Sumatera Utara (cohorts 2022 to 2025) selected through convenience sampling. The research instrument consists of 26 statement items evaluating six main scales: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data analysis was performed using the UEQ Data Analysis Tool to process value transformations, aggregate scale means, and compare results against global benchmarks. Cronbach’s Alpha test results indicate that all variables possess good internal consistency, with scores exceeding 0.6. The findings confirm that SI-SELMA excels in functional aspects; four indicators successfully reached the Above Average level: perspicuity (1.23), dependability (1.29), efficiency (1.14), and stimulation (1.04). However, the visual design aspect shows clear weaknesses, where attractiveness (1.15) and novelty (0.65) fall specifically into the Below Average category. Thus, the platform is reliable in meeting students' administrative needs; however, improvements to the layout and user interface design are recommended to enhance visual appeal and user experience quality in future system development. This study also contributes empirical evidence on the application of the User Experience Questionnaire (UEQ) for evaluating electronic student correspondence systems in higher education and provides interface improvement recommendations based on the user experience evaluation results.